Aphasia Rehabilitation via Codesign, Accessible Discussions and Inclusive Approaches (ARCADIA) project - Charalambous, Marina (My University, 2026)
ARCADIA – Aphasia Rehabilitation via Codesign, Accessible Discussions and Inclusive Approaches EXCELLENCE/0925/0049 | Excellence Hubs Submitted to the Research and Innovation Foundation (RIF), Cyprus for Approval Budget requested: €120,000 ARCADIA is an Excellence Hub proposal aiming to strengthen capacity, innovation, and inclusive practices in aphasia rehabilitation through co-design, accessible communication, and participatory approaches. The project addresses a critical gap in stroke and aphasia services by systematically involving people with aphasia, their families, clinicians, researchers, and community stakeholders as equal partners in the design, implementation, and evaluation of rehabilitation resources and practices. Grounded in principles of Patient and Public Involvement (PPI) and inclusive research, ARCADIA adopts structured co-design methodologies to ensure that rehabilitation pathways, tools, and discussions are accessible, meaningful, and responsive to the lived experiences of people with aphasia. The project places particular emphasis on accessible discussions, using multimodal communication strategies, supported conversation techniques, and visual and participatory tools to enable genuine engagement of individuals with communication difficulties. As an Excellence Hub, ARCADIA aims to: Build national capacity and expertise in inclusive aphasia rehabilitation and co-creation methodologies Foster interdisciplinary collaboration across health, social care, academia, and community organisations Develop and pilot co-designed, accessible rehabilitation resources and practices Strengthen Cyprus’ role as a centre of excellence in participatory stroke and aphasia research and innovation The project integrates research, training, and knowledge exchange activities, supporting healthcare professionals and early-career researchers to adopt inclusive approaches while empowering people with aphasia as contributors, advisors, and co-creators. By embedding co-design and accessibility at all stages, ARCADIA seeks to improve the relevance, quality, and equity of aphasia rehabilitation, while generating transferable models and guidance for wider implementation at national and European levels.